MULTISENSORY DESIGN: PRACTICAL CONCEPT TO EMPOWER PRODUCT PACKAGING DISPLAY IN E-TAILING: Received: 20th March 2021; Revised: 6th April 2021, 14th April 2021; Accepted: 28th May 2021 - Denmamode, Leila (MATTER: International Journal of Science and Technology, 2021)
The digital environment has become the centre of the world with Covid-19 crisis. Businesses have been readjusting their strategies to respond to consumers’ needs and to survive the economic turning point. It is now more than ever vital to exist in a digital world with a distinctive competitive edge. However, investing in emerging technologies is not within the reach of every business owner. Consequently, this paper aims to combine practical technology with multisensory strategy and packaging design to attend to the immediate needs of businesses while addressing the challenge of connecting e-shoppers to products emotionally. The study adopts theories involving website design, packaging design, and multisensory design to construct a new concept intended to empower product display at phases of adding to cart and placing order. Findings showed that above all packaging design’s attributes, features providing touch perception are the chief factors contributing to evaluating products positively in e-tailing. Through websites’ interactive features, e-shoppers perceive a closeness with the product. The present research proposed a new concept named Interactive Appearance to enhance the product experience during online shopping activity. It further demonstrated that packaging design’s features and website design’s features are complementary to provide a positive condition for online shopping.